Pengaruh Voluntary Disclosure dan Leverage terhadap Cost of Equity Capital Pada Perusahaan yang Terdaftar BEI Index IDX30 2019-2021 - Yanisa Zahra Nurul Fitria (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2023)
Public company resources are formed from two main sources, namely shares and debts. In managing company resources, entities must be able to analyze and identify the final output that comes from the funding. Shares or debts will generate a cost of capital or cost of equity. This capital cost includes all business transaction costs related to providing company resources from external parties. Company’s debt will result in installment costs consisting of the principal debt and expenses. A decrease in stock liquidity results in an increase in the rate of return expected by investors and leads to an increase in the company's cost of equity. This study examines the effect of voluntary disclosure and leverage on the cost of equity capital in companies listed on the IDX IDX30 2019-2021. The analysis technique used is Normality Test, Autocorrelation Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Regression Test and Hypothesis Test either partially or simultaneously. Research shows that simultaneously voluntary disclosure and leverage affect the Cost of equity capital. However, partially voluntary disclosure has no effect on the Cost of equity capital. This is inversely proportional to the leverage variable which affects the Cost of equity capital.